Affective, Behavioural and Cognitive Dimensions of Storytelling: Exploring Thai EFL University Students’ Attitudes through Mixed-Methods Analysis - E. Lemana II, Henry; Wong, Wei Lun; Suarez, Zachary D.; Ahmad, Crizjale V.; Jageer Singh, Amreet Kaur (Journal of Education Culture and Society, 2025)
Aim. Storytelling as a pedagogical tool has been studied extensively in early education, but its role in shaping university English as a foreign language (EFL) students’ attitudes in Southeast Asia remains underexplored. This study investigated Thai EFL university students’ attitudes towards storytelling as a pedagogical tool (SATSPT) in the affective, behavioural and cognitive domains and whether there were differences regarding the students’ school affiliation and proficiency levels.Methods. An explanatory sequential research design was adopted through the administration of quantitative surveys that measured the affective, behavioural and cognitive dimensions of attitudes towards SATSPT using the ABC model. The sample consisted of 3,207 first year university students. Then, qualitative interviews were conducted among ten selected students with various levels of English proficiency and from different faculties to further explain their attitudes.Results. Findings show generally positive attitudes with respect to affective (M=3.70), behavioural (M=3.62) and cognitive (M=3.76) domains. Cognitive perceptions were strong. It indicated how effective storytelling is for vocabulary acquisition and linguistic understanding. Affective outcomes included excitement and engagement, but limited reduction in anxiety in speaking tasks. Behaviourally, storytelling elicited strong in-class participation but little voluntary engagement beyond formal venues. The test of ANOVA proved no existence of significant difference on attitudes among faculties (p=0.357) but significant differences among different English proficiency levels (p=0.017). It implies the necessity for differentiated instructional strategies.Conclusion. By employing an ABC model to explain multidimensional student attitudes towards storytelling, this study brings considerable empirical development both to Asian EFL higher education pedagogy and to conceptions of storytelling within proficiency-based learning.